A multi-objective optimization of output parameters of a single cylinder diesel engine running methyl esters and different additives: taguchi-fuzzy based approach / Santhosh Kumar Gugulothu ... [et al.] - Gugulothu, Santhosh Kumar; Panda, Jibitesh Kumar; Sastry, G.R.K; Mishra, Sruti Ranjan (Universiti Teknologi MARA, 2021)
The continuous dependency on fossil fuels for energy requirements, transportation and power generation sectors the research has increased considerably on alternative source of fuel. Recently, it can be seen that Madhuca Indica Methyl Ester is gaining popularity due to its economical nature, the similarity with diesel's properties. The primary aim of this research is to implement blends of Machuca Indica biodiesel using two different additives, 2-EHN and triacetin in different ratios for investigating single cylinder direct injection diesel engine output. In the current analysis, a Taguchi optimisation technique based on fuzzy logic is used to find the optimal combination of emission and performance parameters in order to make prediction of optimal input blends. It shows that the cylinder pressure of the blends is always higher than diesel. Among all blends, BL2 possesses the highest cylinder pressure under various load conditions. In terms of brake thermal efficiency, Among the blends, BL2 and BL3 possess BTE 12%, and 11% more than plain diesel in full load respectively. At maximum load, BSFC of Blend 2, 3 and 6 are (25, 22.5, 20)% less than plain diesel. BL5, BL6 and BL7 produced 3%, 1% and 0.3% less NOx than diesel. It is seen that BL2, BL3 and BL5 had lowermost UHC emission of 34%, 27% and 26% than pure diesel at maximum load. This multi-objective optimization technique shows that the blend BL6 have optimal MPCI value of 0.75.